Defrosting performance of superhydrophobic fin-tube heat exchanger. (25th February 2017) - Wang, Feng; Liang, Caihua; Zhang, Youfa; Zhang, Xiaosong
Highlights: A superhydrophobic fin-tube heat exchanger was prepared. An experimental study on its defrosting performance was performed. It has unique defrosting behavior compared with hydrophilic and bare units. Superhydrophobic heat exchanger shows the highest defrosting efficiency. Abstract: A superhydrophobic fin-tube heat exchanger was prepared, and experimental study was performed to compare its defrosting performance with that of hydrophilic and bare units. Visualization shows that the frost melting behavior is unique on the superhydrophobic unit. After frost layer melting, a film of water forms on the hydrophilic fin surface, and many water bridges form on the bare surface, while it is hard to observe any water on the superhydrophobic surface. Then, temperatures of fin surfaces, defrosting time and energy consumption, and retained water mass were analyzed to further compare the defrosting performance. Compared with the hydrophilic and bare units, the defrosting time of the superhydrophobic unit is shortened by 41.7% and 43.2%, and the energy consumption for defrosting is reduced by 47.2% and 61.9%. The superhydrophobic heat exchanger shows the highest defrosting efficiency.